The Sandwich Dual-Tissue Salvage: Synergistic Anteriorly-Based Tongue Flap and Autologous Dermofat Graft for Recalcitrant Pittsburgh Class V-VI Palatal Fistulas - Anak Agung Gde Rama Kaesara; Putu Trisna Utami (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Recurrent palatal fistulas following cleft palate repair, particularly Pittsburgh Class V and VI defects, represent a distinct reconstructive challenge characterized by tissue ischemia, scarring, and volumetric deficiency. The "failure of failure" in these cases often precludes the use of local mucoperiosteal flaps due to the poor quality of the recipient bed. This study evaluates a standardized "dual-tissue" salvage protocol combining an anteriorly-based dorsal tongue flap with an autologous dermofat graft. Case presentation: A 21-year-old female with a recurrent, symptomatic Pittsburgh Class V-VI fistula measuring 15 mm by 12 mm underwent a two-stage reconstruction. The surgical protocol involved three distinct layers: (1) nasal lining closure via turnover flaps; (2) interposition of an inguinal dermofat graft oriented with the fatty surface facing the nasal layer to obliterate dead space; and (3) oral coverage using an anteriorly-based tongue flap. Speech outcomes were quantified using the Pittsburgh Weighted Speech Scale (PWSS) by an independent, blinded Speech-Language Pathologist. The procedure successfully achieved complete closure with no evidence of necrosis, dehiscence, or donor site morbidity. The total operative time was 145 minutes. Quantitative assessment revealed a robust improvement in speech resonance; the PWSS score improved from a severe 18/30 pre-operatively to a clinically competent 4/30 at 6 months post-operatively. The dermofat graft maintained volumetric stability, preventing the concave collapse often observed in single-layer repairs. Conclusion: The sandwich technique potentially reduces recurrence risk in high-grade fistulas by addressing the triad of failure: tension, ischemia, and dead space. The vascularized tongue flap protects the underlying graft, while the dermofat graft acts as a biological spacer and source of adipose-derived stem cells. This protocol offers a reproducible solution for complex craniofacial defects where local tissues are exhausted.